Exertion of Cultures and Hegemonic Power in Banyuwangi: The Midst of Postmodern Trends - Setiawan, Ikwan; Tallapessy, Albert; Subaharianto, Andang (KARSA Journal of Social and Islamic Culture, 2017)
This article aims to criticize the incorporation and commodification of Using cultures undergone by Abdullah Azwar Anas in Banyuwangi, East Java. To answer the problem, we analyze primary data from our field research and secondary data from online media related to AAAâ€™s efforts to incorporate, articulate, and commodify Using cultures into various carnival programs (2011-2017) by applying theories of commodification, postmodernism, and hegemony. The result of this study shows that, driven by his desire to promote Using cultures globally in the midst of postmodern trends, since 2011 the government of Banyuwangi has created many carnivals and festivals, such as â€œBanyuwangi Ethno Carnivalâ€, â€œBanyuwangi Beach Jazz Festivalâ€, â€œParade Gandrung Sewuâ€, and other various programs. Economically, the programs are idealized to support the regional economic growth through tourism activities, both for domestic and international tourists, by displaying traditional expressions with new styles and performances. Politically, the carnivals and festivals can support AAA efforts to negotiate its political concern in order to produce consensus. Copyright (c) 2017 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v25i1.1118